2014
DOI: 10.1007/s00775-014-1129-2
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the metal-transporting P1B-type ATPases

Abstract: The P1B-ATPases are integral membrane proteins that couple ATP hydrolysis to metal cation transport. Widely distributed across all domains of life, these enzymes have been previously shown to transport copper, zinc, cobalt, and other thiophilic heavy metals. Recent data suggest that these enzymes may also be involved in nickel and/or iron transport. Here we have exploited large amounts of genomic data to examine and classify the various P1B-ATPase subfamilies. Specifically, we have combined new methods of data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
167
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(172 citation statements)
references
References 109 publications
(156 reference statements)
3
167
0
2
Order By: Relevance
“…However, there are multiple subclasses of class P 1B -type ATPases in bacteria, each with various metal specificities. Metal ion specificity has previously been shown to depend on specific amino acid sequences within transmembrane (TM) regions of the protein (26). In order to classify PmtA within P-type ATPase class designations, an amino acid alignment of GAS PmtA with other annotated P 1B-4 -type ATPases from different bacteria (NCBI nonredundant GenBank database) was performed using MUSCLE (27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are multiple subclasses of class P 1B -type ATPases in bacteria, each with various metal specificities. Metal ion specificity has previously been shown to depend on specific amino acid sequences within transmembrane (TM) regions of the protein (26). In order to classify PmtA within P-type ATPase class designations, an amino acid alignment of GAS PmtA with other annotated P 1B-4 -type ATPases from different bacteria (NCBI nonredundant GenBank database) was performed using MUSCLE (27).…”
Section: Resultsmentioning
confidence: 99%
“…Sequences that share homology with S. pyogenes PmtA (see Table S1 in the supplemental material) were identified on the basis of a BLASTP search of the nonredundant GenBank database (NCBI) and included functionally characterized P 1B-4 ATPase amino acid sequences from B. subtilis PfeT (GenBank accession number CUB17201.1), L. monocytogenes FrvA (accession number NP_464168), and GAS PmtA (accession number AAZ51785.1). Determination of the P-type ATPase subclass was performed by using previously described methods (26). Protein sequences were aligned by using MUSCLE v3.8.31 (27) and trimmed to the common transmembrane domains 1 and 6 relative to the well-characterized PfeT protein from Bacillus subtilis (18).…”
Section: Methodsmentioning
confidence: 99%
“…Endocytosis and degradation of a human zinc importer in a histidine-rich, cluster-dependent manner protects against zinc cytotoxicity (63). Several other P 1B -type ATPase family members in mammals and plants to which Pca1p belongs possess undercharacterized metal-binding residues at the N or C terminus (64). The predicted metal binding sites might play roles for regulation of activities, expression, and/or subcellular trafficking of those transporters.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ZntA (a P 1B -type ATPase) and ZntB (a transporter belonging to the 2-TM-GxN family) are zinc exporters (Knoop et al, 2005;Smith et al, 2014 (Beard et al, 1997;Rensing et al, 1997Rensing et al, , 1998Binet & Poole, 2000), Staphylococcus aureus ZntA (ZntA Sa ) exports Co 2+ (Xiong & Jayaswal, 1998), and S. enterica ZntB (ZntB St ) mediates the efflux of Cd 2+ (Worlock & Smith, 2002). The genomic context of A. tumefaciens zntR, zntA and zntB is shown in Fig.…”
Section: Discussionmentioning
confidence: 99%